2021
DOI: 10.3390/jcm10112501
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glucose-Lowering Medications in Erectile Dysfunction

Abstract: Erectile dysfunction (ED) is a long-term complication of type 2 diabetes (T2D) widely known to affect the quality of life. Several aspects of altered metabolism in individuals with T2D may help to compromise the penile vasculature structure and functions, thus exacerbating the imbalance between smooth muscle contractility and relaxation. Among these, advanced glycation end-products and reactive oxygen species derived from a hyperglycaemic state are known to accelerate endothelial dysfunction by lowering nitric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 182 publications
0
13
0
2
Order By: Relevance
“…Indeed, one in five adults are predicted to have obesity by 2025 [ 1 ]. Obesity is also one of the key risk factors for many noncommunicable diseases, such as coronary heart disease, hypertension and stroke, certain types of cancer, type 2 diabetes, gallbladder disease, dyslipidemia, osteoarthritis and gout, and pulmonary diseases, including sleep apnea, and represents one of the principal causes of secondary hypogonadism in men, a condition characterized by the impairment of the hypothalamic–pituitary–testicular (HPT) axis, in which the reduction in testosterone levels is also accompanied by signs and symptoms of hypogonadism, such as decreases in libido, erectile function, semen quality, strength, and mood [ 2 , 3 , 4 , 5 , 6 ]. The prevalence of hypogonadism in normal-weight adult males is around 32%, while about 75% of subjects with severe obesity (BMI > 40 kg/m 2 ) have from hypogonadism [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, one in five adults are predicted to have obesity by 2025 [ 1 ]. Obesity is also one of the key risk factors for many noncommunicable diseases, such as coronary heart disease, hypertension and stroke, certain types of cancer, type 2 diabetes, gallbladder disease, dyslipidemia, osteoarthritis and gout, and pulmonary diseases, including sleep apnea, and represents one of the principal causes of secondary hypogonadism in men, a condition characterized by the impairment of the hypothalamic–pituitary–testicular (HPT) axis, in which the reduction in testosterone levels is also accompanied by signs and symptoms of hypogonadism, such as decreases in libido, erectile function, semen quality, strength, and mood [ 2 , 3 , 4 , 5 , 6 ]. The prevalence of hypogonadism in normal-weight adult males is around 32%, while about 75% of subjects with severe obesity (BMI > 40 kg/m 2 ) have from hypogonadism [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the effect of antidiabetic treatment on erectile function (EF), a limited number of studies focused on humans are available [ 12 , 13 , 14 ], so the data are still limited on ED. A study conducted on Metformin use in diabetic men with ED showed an increased International Index of Erectile Function (IIEF) score after treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study reports the second of two life-threatening episodes of hypoglycaemia followed by unintentional self-poisoning with glimepiride in this patient. Concurrent alcohol ingestion may have accentuated the risk through the inhibition of glycogenolysis ( 6 ). Without the use of a sulphonylurea assay, this patient may have been subject to invasive intraabdominal ultrasound or hazardous partial pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A likely explanation for the remoteness of the ‘Tadapox’ consumption from the hypoglycaemic event is the consumption of alcohol. Alcohol is known to reduce hepatic gluconeogenesis and glycogenolysis, limiting the efficacy of counter-regulatory responses in starvation states or hypoglycaemia ( 5 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation